Caffeic acid encapsulated 3D printed polycaprolactone/ polyvinylpyrrolidone scaffolds for wound healing applications - Zia, Muhammad Khaqan; Akdag, Zekiye; Asghar, Asima; Celik, Sena; Duman, Kevser; Bari, Tayyaba; Ulag, Songul; Dogan, Canan; Gunduz, Oguzhan; Ikram, Fakhera (ELSEVIER, 2025)
Effective wound healing has long been a significant challenge in healthcare, underscoring the need for innovative wound dressings that can speed up the healing process and minimize complications. This study focuses on fabrication and characterization of caffeic acid (CA) loaded polycaprolactone (PCL)/polyvinylpyrrolidone (PVP) scaffolds for wound healing applications. PCL, PCL-PVP, and PCL-PVP 3D printed scaffolds loaded with varying concentrations of CA (20 mg, 30 mg, and 40 mg) were fabricated using 3D printing technology. Chemical and morphological analysis of 3D printed scaffolds were performed by using Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM) respectively. Thermal, mechanical and swelling properties were also examined. Release kinetics of CA showed sustained release of all CA over 264 h after an initial burst at 6 h. In vitro biocompatibility and cell migration assay of 3D printed scaffolds were performed on NIH3T3 mouse fibroblast cell line. Live dead assay also showed the viability of cells in all scaffolds, which confirmed their biocompatibility and suitability for tissue regeneration. Altogether, the PCL-PVP scaffolds containing CA have shown effective biological performance, making them a promising solution for enhanced wound care.
Keywords: 3D printing; Polycaprolactone (PCL); Polyvinylpyrrolidone (PVP); Caffeic acid (CA); Tissue engineering; Wound dressings; PHENETHYL ESTER; IONIC LIQUID; CHITOSAN; ANTIBACTERIAL; PYRROLIDONE; DRESSINGS; MIGRATION; SILVER; DRUGS; ASSAY; Pharmacology & Pharmacy